Education of health care professionals, health associates and expert associates on gender-based violence - Boričić, Katarina (PONS - medicinski časopis, 2020)
ABSTRACT The aim of this study is to determine the quality of accredited education on the topic of gender-based violence to health care professionals, health and professional associates in the Republic of Serbia from January 2010 to July 2019. Method: A search of a database of accredited continuing education programs published on the website of the Health Council of the Republic of Serbia for the period January 2010 to July 2019 identified programs using the keywords "violence", "family" "gender-based". χ2 test was used to examine the differences between the independent variables versus the dependent variable. Results: This study showed that two thirds of the training was intended for health care professionals, while health care workers, health and professional associates were allocated for every seventh education. When looking at the type of institution that organizes the continuing education program, it is noted that twice as many programs are accredited by civil society organizations compared to the number of programs accredited by health institutions. Considering the time period in which the programs are accredited, a trend of increasing number of programs can be observed. Among the accredited programs, national courses accounted for 42.6% of the accredited programs. Every second program provided that participants would pay for the education. There is a statistically significant difference between educations organized by different types of institutions in relation to the type and cost of education. Conclusion: Although there is a growing trend in the observed period in the number of accredited programs addressing gender-based violence, there is still space to improve the quality of continuing education in terms of increasing the number of trainings with an interactive method of work, trainings aimed at different profiles of health professionals and health and professional associates, as well as free on line trainings. Keywords: violence, education, gender based violence, family